Signatures of rapid evolution in urban and rural transcriptomes of white-footed mice (Peromyscus leucopus) in the New York metropolitan area - Harris,Stephen E; Munshi-South,Jason; Obergfell,Craig; O'Neill,Rachel (PeerJ PrePrints, 2013)
Urbanization is a major cause of ecological degradation around the world, and human settlement in large cities is accelerating. New York City (NYC) is one of the oldest and most urbanized cities in North America, but still maintains 20% vegetation cover and substantial populations of some native wildlife. The white-footed mouse, Peromyscus leucopus, is a common resident of NYC’s forest fragments and an emerging model system for examining the evolutionary consequences of urbanization. In this study, we developed transcriptomic resources for urban P. leucopus to examine evolutionary changes in protein-coding regions for an exemplar ‘urban adapter’. We used Roche 454 GS FLX+ high throughput sequencing to derive transcriptomes from multiple tissues from individuals across both urban and rural populations. From these data, we identified 31,015 SNPs and several candidate genes potentially experiencing positive selection in urban populations of P. leucopus. These candidate genes are involved in xenobiotic metabolism, innate immune response, demethylation activity, and other important biological phenomena in novel urban environments. This study is the first to report candidate genes exhibiting signatures of directional selection in divergent urban ecosystems.
Keywords: rapid evolution; transcriptome; Peromyscus; urban ecology; directional selection; candidate gene; nonsynonymous substitution; divergent ecosystem; 454 next-generation sequencing; microevolution